2014
DOI: 10.1063/1.4885855
|View full text |Cite
|
Sign up to set email alerts
|

Production of cold beams of ND3 with variable rotational state distributions by electrostatic extraction of He and Ne buffer-gas-cooled beams

Abstract: The measurement of the rotational state distribution of a velocity-selected, buffer-gas-cooled beam of ND3 is described. In an apparatus recently constructed to study cold ion-molecule collisions, the ND3 beam is extracted from a cryogenically cooled buffer-gas cell using a 2.15 m long electrostatic quadrupole guide with three 90° bends. (2+1) resonance enhanced multiphoton ionization spectra of molecules exiting the guide show that beams of ND3 can be produced with rotational state populations corresponding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…4 The simulated translational temperature of NH 3 equilibrates to 5 ± 1 K at cell lengths of 2 mm and longer. This is in agreement with the experimental buffer-gas-cooled ND 3 translational temperature of 5.96 ± 0.05 K, measured at the end of the quadrupole guide, 16 and with the 6.0 K He buffer gas. The uncertainty in the NH 3 translational temperature primarily arises from the uncertainty in the fit of the velocity distribution to the simulated particles.…”
Section: A Rotational and Translational Energy Distributionssupporting
confidence: 78%
See 2 more Smart Citations
“…4 The simulated translational temperature of NH 3 equilibrates to 5 ± 1 K at cell lengths of 2 mm and longer. This is in agreement with the experimental buffer-gas-cooled ND 3 translational temperature of 5.96 ± 0.05 K, measured at the end of the quadrupole guide, 16 and with the 6.0 K He buffer gas. The uncertainty in the NH 3 translational temperature primarily arises from the uncertainty in the fit of the velocity distribution to the simulated particles.…”
Section: A Rotational and Translational Energy Distributionssupporting
confidence: 78%
“…16, the 20 × 40 × 40 mm (length × height × width) buffer gas cell in the experimental setup is attached to the second stage of a two stage pulse-tube cryocooler.The buffer gas inlet pressure is typically maintained at 0.6 mbar, with an ammonia inlet flow rate of 1.0 SCCM. Helium enters the buffer gas cell at 6 K, as the buffer gas line thermalises with each cryocooler stage prior to entering the buffer gas cell.…”
Section: Modelling An Experimental Buffer Gas Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Several techniques for state detection of cold molecules have been used so far [34,35,36,37,38,39,40]. Among them, depletion methods, as adopted in previous experiments carried out by our group [35,40], are particularly advantageous since they are applicable to a large range of molecules and avoid the difficulties of the light-induced fluorescence (LIF) and resonance-enhanced multi-photon ionization (REMPI) detection techniques.…”
Section: Methods For Rotational-state Detectionmentioning
confidence: 99%
“…In previous studies, such cryogenic effusive sources have been shown to produce, given the right settings, hydrodynamically enhanced, cold molecular beams [62][63][64][65][66]. These beams provide high-density, continuous beams with translational and rotational temperatures in the range of a few Kelvin.…”
Section: General Experimental Considerationsmentioning
confidence: 99%